An Analysis of the Effects of the Number of HAU, Type of Audit Opinion, Size of the Public Accounting Firm, ROA, and DER on Audit Delay in Banking Companies Listed on the Indonesian Stock Exchange - Veronikatani, Veronikatani; Salim, Susanto (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to examine the influence of KAM, type of audit opinion, size of PAF, ROA, and DER on Audit Delay. The research uses a quantitative approach. The sample is selected using purposive sampling method, resulting in 96 banking companies that meet the research criteria. The data is analyzed using the OLS method with Eviews 13 software. The findings show that KAM and type of audit opinion have no significant effect on Audit Delay. This means these two variables do not determine whether audit process becomes faster or slower. In contrast, ROA has a significant negative effect, indicating that higher profitability makes the audit process completed faster because companies with better performance tend to be more prepared in financial reporting. Furthermore, DER also shows a significant negative effect on Audit Delay, implying that highly leveraged firms tend to accelerate the audit process in order to meet creditors’ demands for timely financial information. Simultaneously, all five independent variables significantly influence Audit Delay. However, the R-squared value of 28.19% indicates that the model can only explain part of the variation in Audit Delay, while the rest is influenced by other factors outside the model.